The news media and the agenda for noncommunicable diseases before and during the COVID-19 pandemic: Losing the competition for coverage and framing responsibility for action in Malawi - Dereck L. Hamunakwadi; Stephanie L. Smith (PLoS ONE, 2026)
Chronic noncommunicable diseases (NCDs, such as cardiovascular and diabetes) pose an increasing burden in low-and middle-income countries, accounting for ~80% of premature (under age 70) NCD deaths globally. Despite their significant and rapidly growing burden—and status under United Nations Sustainable Development Goal 3.4—little is known about the agenda status of NCDs in lower-income countries. Though coverage of health issues shapes policymaker and public awareness and opinions, news media is an under-analyzed agenda setting arena. This study explores levels of priority for 10 NCDs compared to four infectious diseases and their burdens in the news media arena in Malawi; shifts in the agenda during the COVID-19 emergency; and media framing of actors responsible for addressing Malawi’s NCD burden. The study is informed by analysis of the contents of headlines (an indicator of media priority) and a purposefully selected subset of articles (framing analysis) published in two news outlets between 2015 and 2023. News media priority for NCDs in Malawi remained relatively low despite elevation to Sustainable Development Goal status. Between 2015 and 2019, news media priority in Malawi heavily favored HIV/AIDS, tuberculosis and malaria over 10 NCDs. Media priority shifted to COVID-19 and headlines on mental health surged ahead of those on HIV/AIDS and tuberculosis during the emergency (2020–2023). Alignment between the burden of disease and media priority was inconsistent. News media framed nongovernmental actors (primarily domestic) as responsible for addressing NCDs (predominantly cancers) far more frequently than other actors, including government, politicians and development partners. Featuring patterns of low attention and framing that fails to hold authorities responsible for addressing NCDs, media priority appears unlikely to substantially shift public opinion or policymaker agendas in their favor in Malawi. This study sets the stage for further analysis of media priority for health issues in lower-income countries.